Assessing the effects of simple and complex innovation strategies on the performance of firms in the Philippines - Connie Bayudan-Dacuycuy; Lora Kryz C. Baje (Philippine Institute for Development Studies (PIDS), 2018)
Innovation is the synergistic use of resources, technology, capital, and information to achieve growth at different levels of the economy. Many studies abroad have already supported the hypothesis that innovation leads to a good firm performance and long-term economic growth. In the Philippines, some studies already analyzed the effects of simple innovations on firm performance. However, emerging literature shows that complex innovation strategies have bigger impacts than simple ones. This paper analyzes the effects of simple and complex innovations on labor productivity and employment growth. Results show that there is no single best innovation strategy that a firm must undertake. However, if firms are constrained by their budget, a simple innovation will help in improving labor productivity and, to some extent, employment growth. Firms that do not face cost issues can benefit more from adopting a complex innovation strategy. In addition, several specific types of complex innovation strategies can be adapted depending on whether the firm aims to increase its employment or to boost its labor productivity.
Keywords: 330; labor productivity; employment growth; simple innovation; complex innovation